NR-g-SAN graft copolymers as impact modifier for SAN - George B (IRRDB Natural Rubber Conference 2008, 13-15 October 2008, Kuala Lumpur, Malaysia: Abstract of papers)
DL
Source Year: 2008
Keywords: NR-g-SAn graft copolymer; SAN